2022
DOI: 10.1128/spectrum.02333-21
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Soil Acidification Could Increase Disease Suppression of Bacterial Wilt by Recruiting Potentially Beneficial Rhizobacteria

Abstract: The rhizosphere microbiota and soil acidification have been shown to have impacts on bacterial wilt. However, the influence of different acidification levels on the rhizosphere communities and bacterial wilt has not been fully studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Their coculture with salt-stressed rice could effectively alleviate salt stress and promote the growth of rice. Bacillus is a relatively common plant growth-promoting rhizobacterium (PGPR) ( 42 , 43 ), and Kushneria is also a growth-promoting bacterium ( 44 ). Interestingly, we found that Bacillus was the dominant species only in the rhizosphere environment and hardly existed in the phyllosphere, while Kushneria was the dominant species only in the phyllosphere (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their coculture with salt-stressed rice could effectively alleviate salt stress and promote the growth of rice. Bacillus is a relatively common plant growth-promoting rhizobacterium (PGPR) ( 42 , 43 ), and Kushneria is also a growth-promoting bacterium ( 44 ). Interestingly, we found that Bacillus was the dominant species only in the rhizosphere environment and hardly existed in the phyllosphere, while Kushneria was the dominant species only in the phyllosphere (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The keystone microorganism OTU74 belonging to Acidobacteriota was positively correlated to disease severity index, and acidophilic Acidobacteria might easily live and grow in the acidic soil. Zhang et al ( 46 ) reported that bacterial wilt was accompanied by soil acidification, and the abundance of R. solanacearum increased when the pH of soil reduced. It was speculated that Acidobacteria might act as a helper of pathogen R. solanacearum .…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth can lead to the accumulation of soilborne pathogens in rhizosphere soil, thus building negative feedback loops between the soil and plants. When challenged by pathogen infection, plants can recruit beneficial microbes to help themselves ( 20 27 ). In this study, we found that belowground plant parts modified the rhizosphere soil microbial community and function by changing plant metabolism and secretion when aboveground leaves were infected by pathogens, eventually changing the plant-soil feedback from negative to positive.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from internal immunological strategies that involve physiological and genetic modifications at the cellular level, plants could employ external strategies that rely on the recruitment of beneficial organisms ( 19 ). A series of studies demonstrated that plants under the stress of long-term soilborne pathogen infection could enrich antagonistic microflora to form disease-suppressive soil to reduce the severity of soilborne disease ( 20 23 ). When Arabidopsis thaliana was challenged with foliar pathogens (such as Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%